Effectiveness of Story Grammar Markers in Enchancing Auditory Memory Children with Learning Disorders in Surakarta - Ibnata, Agrinabila; Gunawan, Gunawan; Pratomo , Hafidz Triantoro Aji (Jurnal Penelitian Inovatif, 2025)
Children with learning disorders often experience challenges in auditory memory processing, which affects their literacy and cognitive skills. Story Grammar Markers (SGM) have been used as an intervention tool to support narrative structure comprehension and memory retention. This study aims to evaluate the effectiveness of SGM in enhancing auditory memory in children with learning disorders in Surakarta. A quasi-experimental research design was implemented using a one-group pretest-posttest method with 15 students aged 7–8 years from various elementary schools. The intervention consisted of five sessions using SGM-based storytelling exercises. The results showed a significant increase in auditory memory scores, with an average pretest score of 16.13 and an average post-test score of 21.40 (p < 0.001). This study confirms that Story Grammar Markers can be an effective educational tool for improving auditory memory in children with learning disorders. These findings suggest the need for further exploration of SGM implementation in inclusive classrooms.